A Comparative Study on the Wettability of Two Coal Samples during Deep Burial Metamorphism. (13th April 2020) - Yan, Guochao; Bai, Longjian; Feng, Jianping; Zhang, Zhiqiang
Abstract : In order to investigate the effect of deep burial metamorphism on the wettability of coal during deep burial metamorphism, a superficial coal sample (∼90 m) and a deep coal sample (∼490 m) collected from two main mining seams were selected to simulate the deep burial metamorphism process. The wettability of two coal samples during deep burial metamorphism was investigated by X-ray photoelectron spectroscopy (XPS), FTIR, zeta potential, and contact angle measurements. Besides, comprehensive DLVO interaction analyses between two coal samples from different mining depths were carried out through the zeta potentials measurements under different pH values. The XPS results demonstrate that the content of surface oxygen atom and oxygen-containing functional group for superficial coal tends to be higher than that of deep coal. The FTIR results indicate that the peak intensity of oxygen-containing functional groups for the superficial is higher than that of deep coal, implying the stronger surface hydrophobicity of deep coal compared to superficial coal. The contact angle of superficial coal is lower than that of deep coal. The zeta potential and DLVO theory analyses of superficial particles and deep coal particles indicate that deep burial metamorphism process might be favorable for bubble-particle collision and attachment, while might be unfavorable for the wetting process oppositely. Based on the surface chemistry characterization and theory analyses, this study is expected to give a theoretical insight into the efficient processing or dedusting process of coals experiencing different deep burial metamorphism processes in the future.